(untitled) (GESTIÓN Y TENDENCIAS, 2017)
In recent years there has been a growing effort to promote innovation in companies in order to increase their competitiveness. It is necessary, however, to specify the type of innovation they should develop, because its effects on business performance differ depending on the productive sector in which it takes place. In this context, the aim of this article is to present different types of innovation and their relevance in different sectors of the Chilean economy.